Influence of life history traits on trophic niche overlap between two similar sympatric Tupinambis lizards - López Juri, Guadalupe (2015)
Segregation of habitat resources is an important mechanism that allows the coexistence of species. The diet is an important and dynamic component that can generate interactions among co-existing species. Differences in food resource use between related sympatric species have been associated frequently with divergence in multiple phenotypic traits; hence, it is interesting to explore how phenotypic differences allow sympatric species to minimize niche overlap. We aimed to evaluate trophic niche segregation between Tupinambis merianae and T. rufescensin relation to life history traits in a sympatric zone. We compared the volume of the stomach food items between species considering sexual dimorphism, body size classes, sexual maturity and reproductive activity. The obtained Morisita?s index indicated trophic niche overlap between T. merianaeand T. rufescens; however, considering particular food items, we observed differences in diet composition. Moreover, our results indicate that body size, sexual maturity and reproductive activity are relevant factors influencing the diet of these species. Life history traits of these two species of Tupinambisare important because they shape diet composition, contributing to interspecific segregation of the trophic niche and, therefore, allowing species coexistence.